PEMANFAATAN JENIS-JENIS TUMBUHAN UNTUK DI JADIKAN OBAT KONSUMSI KELUARGA - Maria Maria Magdalena Duha; Sri Sri Florina Laurence Zagoto (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
This study aims to make use of the types of plants for family consumption medicine. This research is a descriptive study with a qualitative approach with 10 (ten) informants. The data technique used was observation and interview. The data analysis technique used the data analysis method which consisted of three stages, namely data reduction, data presentation and data collection. The conclusion of this study is that there are 13 types of family medicinal plants in Bawodobara Village, namely Zingiber officinale ginger, cocor duck (Bryophyllum pinnatum), turmeric (Curcuma longa), lemongrass (Cymbopogon citratus), galangal (Alpinia galangal L), handeleum (Graptophyllum pictum). ) L), papaya (Carica papaya L), cloves (Syzygium aromatic), hibiscus (Hibiscus rosa sinensis L), green betel (Piper betle L), aloe vera (Aloe vera L), temulawak (Curcuma zanthorhiza) and chilies ( Capsicum annum L) and public knowledge about the types and benefits of family medicinal plants is one of the knowledge that has been passed down from generation to generation by previous parents.